PENGARUH KONSENTRASI EKSTRAK BAWANG MERAH (Allium cepa) TERHADAP PERTUMBUHAN STEK LADA (Piper nigrum L.) - Josina Irene Brigetha Hutubessy (AGRICA, 2012)
This research aims to know the effect of the concentration of shallot extract as well as the optimum concentration of shallots extracts on the growth of pepper plant. The method used in this study was Randomized Block Design with the treatment used is Eo (without concentration), El (the concentration of 100 ppm), E2 (concentration of 200 ppm), E3 (concentration of 300 ppm), E4 (concentration of 400 ppm). Observationvariablesin this study is the height of plant (cm), length of root (cm), the total number of roots, number of shoots, the weight of fresh residues tan-1, dry oven weight of residues. The results showed that no interaction between shallots extracts (Allium cepa L.) and the growth of pepper plant (Piper nigrum L.) which effect on the optimal growth of pepper plant.